2011
DOI: 10.1016/j.jpedsurg.2011.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive repair of congenital diaphragmatic hernia

Abstract: Purpose Operative approach, including minimally invasive surgery (MIS) in the repair of congenital diaphragmatic hernia (CDH), is variable among institutions. The short-term recurrent hernia rate is not well described. We evaluated the in-hospital recurrence rate of MIS repairs of infants with CDH from the Congenital Diaphragmatic Hernia Registry (CDHR). Methods Prospectively collected data from CDH infants were analyzed from the CDHR from January 1995 to January 2010. Recurrent hernia was defined as reopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 13 publications
0
85
0
13
Order By: Relevance
“…Using data from the CDH Study Group, Tsao et al looked at the in-hospital hernia recurrence rate following MIS and found a significantly higher proportion of recurrence in the MIS group compared with open repair; the authors estimated an almost 4-fold increased odds of recurrence with MIS repairs. In this study, infants who required a patch repair had a higher recurrence rate, and MIS repairs that used a patch had the highest recurrence rate of approximately 9% (Tsao et al, 2011). The overall benefit for MIS in CDH patients remains to be determined.…”
Section: Surgical Morbiditymentioning
confidence: 74%
“…Using data from the CDH Study Group, Tsao et al looked at the in-hospital hernia recurrence rate following MIS and found a significantly higher proportion of recurrence in the MIS group compared with open repair; the authors estimated an almost 4-fold increased odds of recurrence with MIS repairs. In this study, infants who required a patch repair had a higher recurrence rate, and MIS repairs that used a patch had the highest recurrence rate of approximately 9% (Tsao et al, 2011). The overall benefit for MIS in CDH patients remains to be determined.…”
Section: Surgical Morbiditymentioning
confidence: 74%
“…Неко-торые авторы [32] определили, что торакоскопия со-провождалась достоверно меньшей продолжитель-ностью ИВЛ и сокращением пребывания больных в госпитале. Обнадеживающие данные получены в работе K. Tsao [9], который установил, что торако-ОРИГИНАЛЬНЫЕ СТАТЬИ скопическое лечение привело к лучшей выживаемо-сти младенцев (98,7% против 82,9%; p<0,05). Иссле-дование А.Ю.…”
Section: дискуссияunclassified
“…В настоящее время торакоскопия постепенно вытесняет торакотомию в лечении врожденных и приобретенных заболеваний органов грудной клет-ки. Начиная с первых публикаций C. van Smith [1] о торакоскопической реконструкции эвисцерации диафрагмы у грудного ребенка в 1998 г. и N. Liem [2] о врожденной диафрагмальной грыже у ново-рожденных в 2003 г. количество сообщений о при-doi: 10.17116/endoskop201521525 -32 Эндохирургическое лечение заболеваний диафрагмы у новорожденных и детей грудного возраста менении видеоассистированного метода в этой воз-растной группе неуклонно растет [3][4][5][6][7][8][9][10][11][12][13][14].…”
unclassified
See 1 more Smart Citation
“…Despite a case selection bias, there is already a significant incidence of recurrences in those repaired by MIS, as opposed to those undergoing an open repair, when examining 151 MIS repairs in the CDH registry out of a total of 4516 patients repaired (Tsao & Lally et al, 2011). Case selection was intended and evident in the disparate use of ECMO (Cho et al, 2009) and targeting groups with favorable criteria such as ventilator stability and absence of stomach or liver herniation (Yang et al, 2005;Kim et al, 2009).…”
Section: Impact Of Minimally Invasive Surgery On Recurrencesmentioning
confidence: 99%